PENGARUH KETAATAN ATURAN AKUNTANSI, KESESUAIAN KOMPENSASI, PERILAKU TIDAK ETIS, KOMITMEN ORGANISASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Ridha Wiranti; Sekar Mayangsari (Jurnal Akuntansi Trisakti, 2016)
This research aimed to examine the influence of compliance on accounting rules, unethical behavior, compliance compensation, and organizational commitment on tendency of accounting fraud. Populations of this research are BUMN company in Jakarta city. The samples in this research are 85 official servants. The technical sampling of this research uses random sampling. Data of this research obtained from directors and accounting staff. Type of data used are primary data. Data collection method used is survey, using questionnaire. Analysis used multiple linear regression. The results indicated that there is the negative effect among compliance to accounting rules and compliance compensation on towards tendency of accounting fraud, there is the positive effect among unethical behavior towards tendency of accounting fraud, and there is no effect among organizational commitment towards tendency of accounting fraud in BUMN